2021
DOI: 10.3389/fped.2021.647038
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Neural Tube Defects in Europe: A Public Health Failure

Abstract: Objective: Thirty years ago it was demonstrated that folic acid taken before pregnancy and in early pregnancy reduced the risk of a neural tube defect (NTD). Despite Public Health Initiatives across Europe recommending that women take 0.4 mg folic acid before becoming pregnant and during the first trimester, the prevalence of NTD pregnancies has not materially decreased in the EU since 1998, in contrast to the dramatic fall observed in the USA. This study aimed to estimate the number of NTD pregnancies that wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Except for Moldova and Kosovo, no other European country implements mandatory folic acid fortification, resulting in more than 1000 pregnancies affected by spina bifida and anencephaly that are preventable every year in Europe. 18 Many countries in Africa and Asia also do not implement folic acid fortification.…”
Section: Current Status and Gaps In Global Fortification Effortsmentioning
confidence: 99%
“…Except for Moldova and Kosovo, no other European country implements mandatory folic acid fortification, resulting in more than 1000 pregnancies affected by spina bifida and anencephaly that are preventable every year in Europe. 18 Many countries in Africa and Asia also do not implement folic acid fortification.…”
Section: Current Status and Gaps In Global Fortification Effortsmentioning
confidence: 99%
“…In many countries, less than 50% of women follow these recommendations [97,98]. Furthermore, pregnancies are not always planned, and some researchers note that fortification of foods with folic acid could substantially lower risks for neural tube defects in Europe [99]. In our study, adult women were the population with the lowest prevalence of folate deficiency, but we should note that the prevalence of vitamin supplements use was also the highest in this group.…”
Section: Discussionmentioning
confidence: 52%
“…In 1996, the Food and Drug Administration (FDA) authorized folate fortification and, by 1998, mandated it [ 112 ]. As of 2021, over 78 countries have mandated folic acid fortification in their flour [ 113 ]. Despite the mounting evidence of a decreased incidence of NTDs with folate supplementation, there are still many countries that forgo fortification and continue to have a significant number of births complicated by NTDs [ 113 ].…”
Section: Folate Metabolismmentioning
confidence: 99%
“…As of 2021, over 78 countries have mandated folic acid fortification in their flour [ 113 ]. Despite the mounting evidence of a decreased incidence of NTDs with folate supplementation, there are still many countries that forgo fortification and continue to have a significant number of births complicated by NTDs [ 113 ]. While it has been demonstrated that folate deficiency is a cause of NTDs, there exist mouse models, as well as human populations, that develop NTDs despite folate supplementation, again underscoring the complex genetic and environmental relationship involved in this process [ 114 ].…”
Section: Folate Metabolismmentioning
confidence: 99%